2002
DOI: 10.1117/12.462874
|View full text |Cite
|
Sign up to set email alerts
|

<title>Reliability of packaged MEMS in shock environment: crack and striction modeling</title>

Abstract: This paper aims at providing a detailed analysis of the consequences of shocking a packaged microstructure to a solid surface. Particularly it concerns the response of homogeneous, packaged clamped-clamped polysilicon microfabricated beams, which can be used in the case of MEMS switches. The theoretical analysis is composed of three parts; first, the micro-machined is considered as a single degree of freedom oscillator the motions of which is governed by an ordinary differential equation. It allows to calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Other researchers modeled the shock problem of MEMS using lumped spring-mass-damper models, such as Srikar and Senturia [18], Li and Shemansky [6], Qian et al [19], Coster et al [20], Bao et al [21], Khatami and Rezazadeh [22], and Ghisi et al [23]. Also, a number of studies accounted for the flexibility of microstructures and treated them as distributed parameters systems in analytical models including the works of Tas et al [24], Fang et al [25], Yee et al [26], and Millet et al [27].…”
Section: Introductionmentioning
confidence: 98%
“…Other researchers modeled the shock problem of MEMS using lumped spring-mass-damper models, such as Srikar and Senturia [18], Li and Shemansky [6], Qian et al [19], Coster et al [20], Bao et al [21], Khatami and Rezazadeh [22], and Ghisi et al [23]. Also, a number of studies accounted for the flexibility of microstructures and treated them as distributed parameters systems in analytical models including the works of Tas et al [24], Fang et al [25], Yee et al [26], and Millet et al [27].…”
Section: Introductionmentioning
confidence: 98%
“…Xiao et al Given that shock leads microstructure to hit the stationary plate, particularly during fabrication, it would be described as an applied force over a short D DAVID PUBLISHING Force, and Mechanical Shock 83 period of time [11,12]. On the other hand, it is undeniable that bending stresses result from shock acceleration in silicon or polysilicon fabricated MEMS [13].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the virtual work done by axial residual force and pressure effect is (11) (12) where, P is the pressure. In accord with the principle of minimum total potential energy, one can be obtained as (13) By substitution of Eqs. (9)- (12) into Eq.…”
mentioning
confidence: 99%
“…Thus, understanding the interaction of mechanical shock, electrostatic forces, and the motion of PCB with that of microstructures is necessary to ensure safe and reliable operation ofMEMS devices. A number of investigations have been conducted in recent years to investigate mechanical shock in MEMS [1][2][3][4][5][6][7][8][9]. Comprehensive reviews of these can be found in [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%